FORMATION OF PHASES IN COMPLEX OXIDES WITH A PYROCHLORE STRUCTURE CONTAINING LITHIUM IONS - Kh.N. Bozorov (Research Focus International Scientific Journal, 2023)
Formation laws of potassium and lithium antimonate-tungstates during heating of complex oxide (y-x)K2CO3-xLi2CO3-ySb2O3-2(2-y)WO3 mixture in air were studied. For a temperature of 1123 K in the KSbO3-WO3-LiSbO3 concentration triangle, the formation zone of LixKy-xSbyW2-yO6 containing phases with a pyrochlore-type structure was determined.